Multicentric data analysis of the learning curve for laparoscopic Shull's repair of pelvic floor defects - Cianci, S.; Ronsini, C.; Riemma, G.; Palmara, V.; Romeo, P.; La Verde, M.; Laganà, A. S.; Capozzi, V.; Andreoli, G.; Palumbo, M.; Torella, M. (Frontiers in Surgery, 2024)
Introduction: Pelvic organs prolapse remains a significant health concern affecting millions of women worldwide. The use of native tissues to suspend the apex has acquired relevance in urogynecologic surgery. One of the most commonly used procedures performed without mesh is the technique described by Shull, consisting of suturing the vaginal apex to the uterosacral ligaments. The objective of the study is to evaluate the learning curve of laparoscopic Shull's repair for the correction of pelvic floor defects, including the surgery time and surgical outcomes.